Silvicultural evaluation of Brazil nut tree (Bertholletia excelsa H.B.K.) in two plantations located in the state of Rondônia, Amazon Region, Brazil. - LOCATELLI, M. (2013)
The objective of this study was to analyze brazil nut height and breast height diameter (DBH) tree growth, evaluate the sociological position, and stem and crown characteristics.